Study Impact of Overall Equipment and Resource Effectiveness onto Cement Industry (Journal of University of Babylon for Engineering Sciences, 2018)
The existence and development of an organization relies on the employment level of equipment and obtainable resources. Whole the resources as worker, equipment, and raw material are to be employed to the level of manufacture criterion, Also the potential impact this relationship may have on decision-making that contributes to improve the productivity of the manufacturing organization. This research aims to employ two operation performance  indicators: overall equipment and resource effectiveness  to study impact them onto manufacturing system. AL-Kufa /Iraq Cement plant is employed as a case study, also Bar chart tool is used to assess present results. Results are generated using Minitab Version 17. Results show that finish grinding process has lowest factors of performance, quality rate, availability of material, readiness, and availability of facility which lead to reduce OEE and ORE performance indicators of 65.02 % and 15.45%.